COMPARITION OF PHSIOLOGICAL EFFECT OF TWO ANTIHELMENTIC PROGRAMS ON BLOOD CONSTITUENTS IN AWASSI EWES - Gabar ALMasri; Nabeel Abdul (Mesopotamia Journal of Agriculture)
This study was conducted in the Animal resources department field College of Agri. and Forestry by using two antihelmentic programs for awassi ewes . 20 awassi ewes (3 – 4 year age) were divided into two groups (10 animal/ group). The 1st group treated with Albendazole (7.5mg/kg B.wt) orally and Ivermectin (2mg/kg B.wt) s.c. The 2nd group treated with Rafoxanide (7.5mg/kg B.wt) orally and Ivermectin (2mg/kg B.wt) s.c. Results revealed a significant increase in Hb. concentration in the group treated with albendazole and ivermectin , and a significant increase in Hb. concentration , PCV , T.RBC , serum total protein , globulin and globulin: albumin ratio in the group treated with rafoxanide and ivermectin. In conclusion results revealed that the rafoxanide and ivermectin antihelmentic programs were better than the albendazole and ivermectin program in improving blood picture and the serum biochemical parameher in awassi ewes.